Risk Reality Geospatial Information Modeling: An Application in Lupi, Camarines Sur, Philippines - Abante, Ana Marie R. (International Journal of Computing Sciences Research; Vol 5 (2021): Vol 5, 2021)
Purpose – This study sought to locate and visualize the land use constrained relative to its calamities and disaster risk reality in Lupi, Camarines Sur by developing a risk reality geospatial information model that constitutes the level of significance that signifies the consequences of natural calamities or man-made hazards an important point that local government units cannot afford to ignore. Method – The Risk Reality Geospatial Information Model applied the hexagonal binning technique (Abante, 2020a; Abante, 2020b) and the Abante’s Risk Reality Isosceles Triangle (ARRIT)with angle alpha 36based on Schoen Golden Triangle which represents the risk-neutral stance equal to one unit was used to study the important factor that shaped the state of balance or stability where one asymptotic segment on receptiveness with an opposite angle of 72 which signifies the prevention, mitigation, and preparedness and the other is responsiveness which response and recovery stages of DRRM (Abante, 2020a, 2020b; Oksanen, 2013; Oat, Barczak & Shopf, 2008). The hexagonal binning technique leads to complexities in quantifying risk hotspots and coldspots (Abante, 2020a, 2020b; Gold, 2016; Oksanen, 2013; Oat et al., 2008; Worboys & Duckham, 2004; Getis & Getis, 1966). It is regarded as storing weighted values ranging from 1 which is the lowest to 5 which pertains to the highest value (Abante, 2020a, 2020b). The weights may be influenced by hazard return periods or proximity to the critical condition of the landscapes or seascapes that are highly prone or regularly impacted by hazards (Abante, 2020a, 2020b). The Binning Parameters following data binning parameters were created and applied to study variations of the six elements of risk reality (Abante, 2020a, 2020b). Results –This study disclosed the risk hotspots in Lupi that are reckoned in the stability line (base) of an ARRIT that was based on Schoen's theory of the golden triangle and Fibonacci's golden ratio as it orbits the golden spiral (Abante, 2020a, 2020b). The risk-neutral stance represents the balance between receptive and responsive DRRM measured by the resulting z-scores derived from data on hazards, vulnerability, exposure, and capability (Abante, 2020a, 2020b). The capability in this study constitutes the preparedness in terms of land development, utilization, and base zones. (Abante, 2020a, 2020b) TheRisk Reality Geospatial Information Model for Lupi proved that visualization of land use constraints relative to base zones where restructuring of DRRM actions are needed to attain physical and environmental balance (Abante, 2020a, 2020b; Abante & Abante, 2019; Abante & Abante, 2018;Barua&Ansary, 2020). Conclusion – The author concluded that an informed local government is prepared although it seems long term to achieve it but desire to make real progress towards risk reduction. It is also concluded that the model can mimic the municipality's risk reality extremes that need to be avoided and knowing it is something that matters to guide and control land use and local development to achieve physical and environmental balance. The DRRM cycle urges the LGUs to make land-use allocations free if not reduced risk through prevention, mitigation, and preparedness. Recommendations – The author proposed to further apply hexagonal data mining techniques ideal for cities and municipalities to dig deep into the land utilization free from risk if not reduced risk through proper zoning the best-highest-land use(Abante, 2020a, 2020b;Abante& Abante, 2019; Abante & Abante, 2018; Fischel, 2000).Furthermore, a fine-tuned DRRM backed by an approved land use plan and zoning ordinance can be workable through continuous monitoring and evaluating the risk hotspot areas and areas with land development constraints to attain and sustain local development growth in cities and municipalities